Improving Elementary School Students' Understanding of the Concept of Flat Geometry Elements Through an Open-Ended Approach - Mufaricha Ulia Anjani; Akhmad Jufriadi; Qomariyah (Journal of Practice Learning and Educational Development, 2026)
This study aims to improve the understanding of the concept of the elements of plane figures in grade III students of Tanjungrejo 5 Public Elementary School through the application of an open-ended approach. The main problem found in the pre-action was the low ability of students to understand geometric concepts due to reliance on memorization and one definite answer. This Classroom Action Research (CAR) was carried out in two cycles using the Kemmis & McTaggart model which includes the stages of planning, implementation, observation, and reflection. The learning steps applied included open problem orientation, problem presentation, independent or group problem solving, and discussion of the results of the solution. The results showed a significant increase in conceptual understanding gradually. Students' classical mastery in the pre-action only reached 3.70% with a very poor category. After the action was carried out in cycle I, the mastery rate increased to 64.28%. In cycle II, classical mastery jumped to 92.80% and was included in the excellent category. This increase is supported by the theory of constructivism and the theory of cognitive flexibility which emphasize that knowledge is actively constructed by students through problems that challenge creativity. This approach has proven effective in making students more creative and able to solve mathematical problems with more than one solution.